Design of Elementary School Inclusive Education in Garut Regency - Angga; Cucu Suryana; Ima Nurwahidah; Nenden Ineu Herawati (International Conference on Elementary Education, 2023)
Inclusive education is an innovative approach to accommodate the learning needs of children with special needs. In the broader context, inclusive education can be interpreted as a step in education services in completing compulsory education for all Indonesians. This inclusive education provides insight and knowledge to the community to be able to facilitate the learning needs of children with special conditions. Inclusive education can be one of the efforts in creating educational programs for all walks of life, without being hindered by the conditions that the person has. This study aims to analyze the extent of the design of inclusive education that can be implemented in elementary schools in Garut Regency. The method used in this study is Literature Method. The results showed that there were quite a lot of children with special needs of elementary school age in the Garut Regency. Meanwhile, the distance to the Extraordinary School is quite far. This is because, the Garut area is divided into North Garut, Garut Kota, and South Garut. Not all sub-districts have Extraordinary Schools, even if there are only for certain types of Extraordinary Schools, so this Inclusive Education needs to be organized for the elementary school level in Garut Regency. Thus, the implementation of an Inclusive Education at the elementary school level in Garut Regency requires cooperation and careful design, starting from the preparation stage to the evaluation of education implementation. In addition, appropriate action is needed from various parties, starting from the school ecosystem, such as teachers, principals, supervisors, parents, and policymakers, including the Education Office in the Garut and West Java regencies.